Estimation of physiotherapeutic effects in the treatment of spinal osteochondrosis complicated by pain syndrome with the use of pulsed magnetic stimulation - Loboiko, V. V. (Journal of Education, Health and Sport, 2017)
The article is devoted to the study of the possibility of applying modern approaches to the treatment of algic phenomena caused by degenerative changes in the spine and evaluation of emerging pathogenic therapeutic effects. Our proposed recovery regimen with pulsed magnetic stimulation provides an increase in the effectiveness of treatment of osteochondrosis of the lumbar spine, complicated by pain syndrome due to the potentiation of sanogenetic mechanisms for improving the functional state of the neuro-vascular-muscle segments of the spine, regression of pain syndrome and increased physical performance.